Physico-chemical properties of chicken nugget by addition gelatin from the skin and bones of goat with pretreatment L.plantarum and acetic acid. Issue 1 (June 2021) - Hasma,; Abustam, E; Malaka, R; Said, M I
Abstract: This study aimed to obtain the best quality of chicken nuggets by adding gelatin from goatskin and bones pretreated with L.plantarum and acetic acid. The research method was used a completely randomized design (CRD) with the following treatments: (1)control; (2) goatskin gelatinL.plantarumpretreatment(GsgLp); (3) goatskin gelatin acetic acid pretreatment (GsgAa); (4) goat bone gelatinL.plantarumpre-treatment (GbgLp); (5) goat bone gelatin acetic acid pre-treatment (GbgAa). The results showed a very significant effect (P<0.01) on pH, nugget shear force, brightness L*, reddish a* and yellowish b*. The chicken nuggets added with GbgLp showed the highest of pH value and brightness L* color, but the nugget shear force showed the lowest value. The chicken nuggets added by GbgAa showed the highest a* reddish color value, as did chicken nuggets with the addition of GsgLp showed the highest yellowish color value. Conclusion, the chicken nuggets added with GbgLp showed better quality.